2021
DOI: 10.1002/anie.202103398
|View full text |Cite
|
Sign up to set email alerts
|

Tricycloquinazoline‐Based 2D Conductive Metal–Organic Frameworks as Promising Electrocatalysts for CO2Reduction

Abstract: 2D conductive metal–organic frameworks (2D c‐MOFs) are promising candidates for efficient electrocatalysts for the CO2 reduction reaction (CO2RR). A nitrogen‐rich tricycloquinazoline (TQ) based multitopic catechol ligand was used to coordinate with transition‐metal ions (Cu2+ and Ni2+), which formed 2D graphene‐like porous sheets: M3(HHTQ)2 (M=Cu, Ni; HHTQ=2,3,7,8,12,13‐Hexahydroxytricycloquinazoline). M3(HHTQ)2 can be regarded as a single‐atom catalyst where Cu or Ni centers are uniformly distributed in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
144
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(148 citation statements)
references
References 37 publications
2
144
1
1
Order By: Relevance
“…The dominant peaks at 4.0°, 8.0°, 10.6° and 13.9°, according to [100], [200], [210] and [220] reflections, indicate long‐range order within the ab plane. The position and intensity of the diffraction peaks are well consistent with the reported 2D honeycomb lattice of Cu‐HHTQ with eclipsed (AA) staking pattern [15, 19] . A 2D hexagonal lattice with AA staking patterns (cell parameter: a = b =25.41 Å, c= 3.19 Å, α = β =90, γ =120° in P62m space group) was simulated accordingly.…”
Section: Methodssupporting
confidence: 76%
“…The dominant peaks at 4.0°, 8.0°, 10.6° and 13.9°, according to [100], [200], [210] and [220] reflections, indicate long‐range order within the ab plane. The position and intensity of the diffraction peaks are well consistent with the reported 2D honeycomb lattice of Cu‐HHTQ with eclipsed (AA) staking pattern [15, 19] . A 2D hexagonal lattice with AA staking patterns (cell parameter: a = b =25.41 Å, c= 3.19 Å, α = β =90, γ =120° in P62m space group) was simulated accordingly.…”
Section: Methodssupporting
confidence: 76%
“…Although many MOF-or COF-based ECR catalysts with unchanged structure after ECR tests have been reported [31][32][33] , the phase transition might occur in some crystalline materials during electrocatalysis, leading to the change of the instinct catalytic sites 28,38,42 . Thus, the structural stabilities of the Cu-DBC electrocatalyst before and after electrocatalysis have been characterized and investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al also reported a bimetallic two-dimensional cMOF embedded with phthalocyanine Cu-N 4 sites and zincbis(dihydroxy) Zn-O 4 sites for the selectivity modulation towards ECR-to-CO and HER 32 . More recently, a nitrogen-rich cMOF with graphene-like porous structure, Cu 3 (HHTQ) 2 , was synthesized and served as ECR catalysts, showing a high selectivity to CH 3 OH with Faradaic efficiency (FE) reached up to 53.6% 33 . Despite the progress in ECR applications with cMOF, there is still few research on cMOF electrocatalysts for efficient ECR-to-hydrocarbons with enhanced activity and satisfactory hydrocarbons selectivity.…”
mentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), as an emerging versatile platform with metal nodes bonded with organic ligands, [18–20] are effective electrocatalysts for aprotic Li−O 2 batteries, which can simultaneously afford high discharge capacity and moderate charge kinetics [21–23] . However, the bulk MOF cathodes suffer from inferior conductivity and blockage of active metal sites by guest ligands, resulting in a large voltage hysteresis of over 1.5 V. Rational design and synthesis of two/one‐dimensional conductive MOFs enables facile electron transfer, exposure of active surfaces, and unsaturated metal centers, which promise to raise the number of active sites to enhance the electrocatalytic activity [24–28] . The well‐defined structures also provide an ideal platform to probe the underlying structure‐performance relationship at the atomic or molecular levels.…”
Section: Introductionmentioning
confidence: 99%